Currency Order Flow and Exchange Rate Determination: Empirical Evidence from the Malaysian Foreign Exchange Market - Anifowose, Abolaji Daniel; Ismail, Izlin; Sukor, Mohd Edil Abd (SAGE Publications, 2018)
This article presents empirical test results of Malaysian foreign exchange market microstructure assessment of exchange rate dynamics. We apply vector autoregressive (VAR) model to estimate the influential role of currency order flow in the determination of the currency exchange rate for the Malaysian ringgit (MYR) against the US dollar (USD). We investigate whether currency order flow captures the movements of exchange rate of MYR against USD, and how the long-term and short-term components impact the relative estimation of MYR in the international market. We, construct a measure of order flow in the Malaysian foreign exchange market to reflect the pressure of currency excess demand. Our focus is on the cumulative currency order flow and the exchange rate relationship of MYR and USD. A hybrid model of order flow and exchange rate dynamics proposed by Evans and Lyons (2002a) is applied to the Malaysian foreign exchange market (MYR/USD) to analyse a dataset of every 15-minute currency order flow and exchange rate movements from January 2010 to December 2015. Our dataset has unique features in terms of the quality of the data, extensive period and precise high frequency. Our results show that currency order flow explains an important portion of the movements in the MYR–USD exchange rate.